AWARENESS OF HERPETIC NEURITIS AMONG DENTAL PRACTITIONERS - M, Aparna; Ganapathy, Dhanraj; Rohinikumar, Subhashree (International Journal of Psychosocial Rehabilitation, 2019)
Herpetic neuritis is indeed a painful infection that damages both the nerve fibers as well as the skin. This is a shingles side effect. It is also the resurgence of varicella zoster virus, or chickenpox virus, that has been latent in the sensory root ganglia of the neural system from early life. The purpose of the survey was for determining the knowledge,awareness and management practices of herpetic neuritis in a dental clinical setup among dental practitioners. A total of 100 dental practitioners were randomly enrolled in the study and voluntarily completed a questionnaire consisting of 10 close – ended questions. Questionnaire consist of questions based on demographic characteristics, knowledge on risk factors , causes , signs and symptoms ,various diagnostic aids, management of herpetic neuritis etc.Questionnaire data was gathered by sharing survey planet link to the selected population. Data was entered in Microsoft excel sheets and statistically analysed . Around 99% of the dental practitioners are aware of symptoms of herpetic neuritis. Almost all the dental practitioners attended the survey are aware of the various risk factors of herpetic neuritis and its most important and common diagnostic factor.About 91.1% of the population are aware of the primary prevention of herpetic neuritisAbout 96% of the participants were aware about the various diagnostic aids and management practices of herpetic neuritis patients and implement them in their clinical practice.The knowledge and awareness among dentists about herpetic neuritis patients in a clinical setup is adequate and some of dentists had negative attitude towards the management practices..Organising seminars and additional classes about herpetic neuritis and its management protocol may help to gain more knowledge about the disease.